Translation of Folktales from Runyankore-Rukiga into English: - Tumuheirwe, Kizito (Kabale University, 2025)
This study aims at translation of Runyankore-Rukiga folktales into English, identifying cultural and linguistic challenges and suggesting strategies to aid cross-cultural translation. Five folktales have been translated with explanatory footnotes about the hard-to-translate and/ or untranslatable words and expressions. The researcher back-translated two of them to verify the validity of the translation. The study was qualitative in nature. It relied on data from both primary and secondary sources. The study showed that translation faces culture related challenges, given that the languages are culturally distinct. It also showed that meaningful, “speaking” personal names and literary devices such as euphemisms, proverbs and proverbial expressions, idioms and idiomatic expressions, ideophones and onomatopoeia, similes and metaphors are sources of problems in translation. Some strategies to resolve these challenges have also been suggested: firstly, employing footnotes to explain the hard-to-translate and untranslatable culture-bound and linguistic items and expressions; secondly, using the three proverb and proverbial translation principles proposed by Beekman & Callow (1974, p. 139); and adopting the principle that some devices remain untranslated and are retained in the target language (Kaindl, 1999, p. 275). In addition, the researcher used the methods: literal translation and free translation for euphemisms, as proposed by Wang (2020, pp. 1176 -1177); plus Baker’s (1992) taxonomy of four idiom translation strategies. Lastly, the five simile and metaphor translation strategies proposed by Larson (1984, p. 254) were applied. The study recommended, firstly, that the government invests in and puts more emphasis on translation work and studies of this nature; secondly, that translators ensure they fully understand the source and the target languages and cultures; lastly, that translation be introduced into the language syllabus at secondary school level.